Analysis of Carbon Emission Levels in the SSH Forest Area Based on Land Cover Change - Oktama R, Dhea; Ikhwan Siregar, Yusni; Suwondo, Suwondo (Devotion : Journal of Research and Community Service, 2024)
The Sultan Syarif Hasyim (SSH) Forest Park (Tahura) area in Riau Province is a forest conservation area that has an important role in maintaining the balance of the ecosystem, especially in terms of carbon sequestration and carbon emission reduction. This study aims to measure the level of carbon emissions resulting from land cover changes and analyze the main causative factors of carbon emissions in the Tahura SSH area. The methods used include field analysis, measurement of carbon emissions based on land cover changes, and data processing using emission modeling software. The results show that carbon emissions in this region are mainly caused by deforestation and land clearing activities, which accelerate the release of carbon stored in forest biomass. In addition, this study provides recommendations for mitigation strategies that can be carried out, such as forest rehabilitation efforts, sustainable land management, and strengthening conservation policies. This research is expected to be an important reference in efforts to reduce carbon emissions in conservation forest areas and encourage policies that support environmental sustainability.